Developing nurses' intercultural/intraprofessional communication skills using the EXCELLence in Cultural Experiential Learning and Leadership Social Interaction Maps. Issue 17 (4th December 2017) - Henderson, Saras; Barker, Michelle
Abstract : Aims and objectives: To examine how the use of Social Interaction Maps, a tool in the EXCELLence in Cultural Experiential Learning and Leadership Program, can enhance the development of nurses' intercultural/intraprofessional communication skills. Background: Nurses face communication challenges when interacting with others from similar background as well as those from a culturally and linguistically diverse background. We used the EXCELLence in Cultural Experiential Learning and Leadership Program's Social Interaction Maps tool to foster intercultural/intraprofessional communication skills in nurses. Social Interaction Maps describe verbal and nonverbal communication behaviours that model ways of communicating in a culturally appropriate manner. The maps include four stages of an interaction, namely Approach, Bridging, Communicating and Departing using the acronym ABCD. Design: Qualitative approach was used with a purposeful sample of nurses enrolled in a postgraduate course. Methods: Fifteen participants were recruited. The Social Interaction Map tool was taught to participants in a workshop where they engaged in sociocultural communication activities using scenarios. Participants were asked to apply Social Interaction Maps in their workplaces. Six weeks later, participants completed a semistructured open‐ended questionnaire and participated in a discussion forum on their experience of using Social Interaction Maps. Data were content‐analysed. Results: Four themes identified in the use of the Social Interaction Maps were (i) enhancing self‐awareness of communication skills; (ii) promoting skills in being nonconfrontational during difficult interactions; (iii) highlighting the importance of A (Approach) and B (Bridging) in interaction with others; and (iv) awareness of how others interpret what is said C (Communicating) and discussing to resolve issues before closure D (Departing). Conclusions: Application of the EXCELLence in Cultural Experiential Learning and Leadership Social Interaction Mapping tool was shown to be useful in developing intercultural/intraprofessional communication skills in nurses. Relevance to clinical practice: Professional development programmes that incorporate EXCELLence in Cultural Experiential Learning and Leadership Social Interaction Maps can enhance nurses' intercultural/intraprofessional communication competencies when engaging with others from culturally and linguistically diverse backgrounds and improve the way nurses communicate with each other.